Myopes have significantly higher serum melatonin concentrations than non‐myopes. (18th July 2017) - Kearney, Stephanie; O'Donoghue, Lisa; Pourshahidi, L. Kirsty; Cobice, Diego; Saunders, Kathryn J.
Abstract: Purpose: Experimental animal models of myopia demonstrate that higher melatonin (Mel) and lower dopamine (DA) concentrations actively promote axial elongation. This study explored the association between myopia and serum concentrations of DA and Mel in humans. Methods: Morning serum concentrations of DA and Mel were measured by solid phase extraction ‐ liquid chromatography ‐ tandem mass spectrometry from 54 participants (age 19.1 ± 0.81 years) in September/October 2014 (phase 1) and March/April 2016 (phase 2). Axial length (AL), corneal radii (CR) and spherical equivalent refraction (SER) were also recorded. Participants were defined as myopic if non‐cycloplegic spherical equivalent refractive error ≤−0.50 DS at phase 1. Results: Nine participants were lost to follow up. Mel concentrations were measurable for all myopes (phase 1 n = 25, phase 2 n = 22) and non‐myopes (phase 1 n = 29, phase 2 n = 23). SER did not change significantly between phases ( p = 0.51). DA concentrations were measurable for fewer myopes (phase 1 n = 13, phase 2 n = 12) and non‐myopes (phase 1 n = 23, phase 2 n = 16). Myopes exhibited significantly higher Mel concentrations than non‐myopes at phase 1 (Median difference: 10 pg mL −1, p < 0.001) and at phase 2 (Median difference: 7.3 pg mL −1, p < 0.001) and lower DA concentrations at phase 2 (Median difference: 4.7 pg mL −1, p = 0.006). Mel concentrations were positively associated with more negative SER (all r ≥ −0.53, all p < 0.001), longer AL (all r ≥ 0.37, all p ≤ 0.008) and higher AL/CR ratio (all r ≥ 0.51, all p < 0.001). Conclusion: This study reports for the first time in humans that myopes exhibit higher serum Mel concentrations than non‐myopes. This may indicate a role for light exposure and circadian rhythm in the human myopic growth mechanism. Further research should focus on younger cohorts exhibiting more dynamic myopic progression and explore the profile of these neurochemicals alongside evaluation of sleep patterns in myopic and non‐myopic groups.